Composite boronizing agent and solid boronizing method for oil pipe
By using a composite boron leaf agent, including boron extension and graphite, and the use of decentralized decentralizers in ethanol, solve the problem of influence of the surface impurities in the oil pipe affecting the quality of the boron vesry layer, and realized the formation of high -quality boron pouring layers and the formation and The boron osmotic agent is evenly distributed, avoiding the problem of carburizing and blocking, and improves the corrosion resistance and service life of the oil pipe.
Patent Information
- Application Number
- CN202411328619.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-24
AI Technical Summary
The existing solid boron dehydration process has impurities on the inner surface of the oil pipe that affect the quality of the boron dehydration layer, which is prone to carburization and fall off of the boron dehydration layer, and the problem of difficulty in removing boron dehydration agent agglomeration.
Compound boron leaflets, including boron oligomers and graphite, borne amine bornes are used as decentrals, wrapped boron supplies and catalysts to achieve secondary rust removal effects, and boron seepage blocks are avoided by graphite.
It improves the quality and bonding strength of the boronized layer, avoids the carburizing phenomenon and boronizing agent agglomeration, simplifies the removal process, and improves the corrosion resistance and service life of the oil pipe.
Smart Images

Figure CN118835195B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal surface treatment, in particular to a composite boronizing agent and a solid boronizing method for an oil pipe. Background Art
[0002] Oil is an important energy source and an important strategic material, buried deep underground or under the ocean. Equipment for oil extraction includes but is not limited to steel oil pipes. Oil pipes are used to transport crude oil or refined oil over long distances. They are easily corroded by pressure, temperature, and various corrosive media. Therefore, it is necessary to improve the durability of oil pipes and reduce the frequency of replacement.
[0003] Boriding is a chemical heat treatment technology that allows the boron element to penetrate into the metal surface under high temperature conditions to obtain a hard layer of boron compounds. The hardness, wear resistance and corrosion resistance of the inner surface of the oil pipe can be improved by boriding the inner surface of the oil pipe.
[0004] The existing technology can be used to boronize the oil pipe through solid boronizing, gas boronizing, paste boronizing, and salt bath boronizing. Among them, solid boronizing has the advantages of convenient process operation, simple equipment, and easy quality control, and has been widely used in production. However, although the solid boronizing process has many advantages, it still has some disadvantages, which limits the application of the solid boronizing process in oil pipes.
[0005] First, it is difficult to completely remove impurities such as metal oxides on the inner surface of the oil pipe, and these impurities will affect the quality of the boronized layer.
[0006] Second, as the boronizing process proceeds, carburization will gradually occur on the inner surface of the oil pipe and a carburized layer will be produced. The carburized layer will prevent boronizing and form holes, making the boronizing agent unusable. In addition, the boronized layer that has been formed will not be firmly bonded to the oil pipe and will easily fall off.
[0007] Third, in the existing solid boronizing method, after the boronizing treatment, the boronizing agent will agglomerate on the inner surface of the oil pipe. After the boronizing agent agglomerates, it takes extra manpower and material resources to remove it. Moreover, for long oil pipes, such as oil pipes with a length of 9.7m or more, it is difficult to completely remove the boronizing agent agglomerated on the inner surface of the oil pipe.
[0008] Therefore, it is necessary to solve the problems existing in the prior art that the quality of the boronized layer is easily affected by impurities on the inner surface of the oil pipe, carburization occurs and only carburization without boronization occurs, the boronized layer is easy to fall off, and the boronizing agent agglomerates and adheres to the inner surface of the oil pipe and is difficult to remove. Summary of the invention
[0009] 1. Technical issues to be resolved
[0010] In view of the above technical problems, the present invention provides a composite boronizing agent and a solid boronizing method for oil pipes to improve the quality of the boronized layer, avoid the phenomenon of only carburizing without boronizing, improve the bonding strength of the boronized layer and avoid agglomeration of the boronizing agent.
[0011] (II) Technical solution
[0012] In order to achieve the above object, the main technical solutions adopted by the present invention include:
[0013] The present invention provides a composite boronizing agent, comprising a boronizing agent and graphite;
[0014] Among them, according to the mass percentage, graphite accounts for 10-14% of the mass of the boronizing agent; the boronizing agent includes the following raw materials in mass percentage: boron supply agent: 10-15%, catalyst: 12-20%, activator: 8-10%, dispersant: 4-6%, filler: 50-55%, flow aid: 8-12%; the dispersant is triethanolamine borate.
[0015] In the composite boronizing agent as described above, preferably, the boron supplying agent is boric anhydride or boron carbide.
[0016] In the composite boriding agent as described above, preferably, the catalyst comprises potassium fluoroborate, sodium fluoride and potassium fluoride, wherein potassium fluoroborate accounts for 5-10% of the total mass of the boriding agent, sodium fluoride accounts for 5-6% of the total mass of the boriding agent, and potassium fluoride accounts for 2-4% of the total mass of the boriding agent.
[0017] In the composite boriding agent as described above, preferably, the activator comprises silicon dioxide and activated carbon, wherein silicon dioxide accounts for 5-7% of the total mass of the boriding agent, and activated carbon accounts for 2-4% of the total mass of the boriding agent;
[0018] The filler includes aluminum oxide and / or silicon carbide.
[0019] The composite boronizing agent as described above, preferably, the particle size of the graphite mixed with the boronizing agent is 30-50 mesh;
[0020] The flow aid includes charcoal powder and graphite powder, wherein the charcoal powder accounts for 3-5% of the total mass of the boronizing agent, and the graphite powder accounts for 4-8% of the total mass of the boronizing agent; the particle size of the graphite powder is 140-160 meshes.
[0021] The present invention also provides a solid boronizing method for an oil pipe using the composite boronizing agent, comprising the following steps:
[0022] S1: Clean the inner surface of the oil pipe;
[0023] S2: mixing the boriding agent with graphite to obtain a composite boriding agent, and then filling the composite boriding agent into the oil pipe so that the composite boriding agent contacts the inner surface of the oil pipe;
[0024] S3: sealing the oil pipe filled with composite boronizing agent;
[0025] S4: The sealed oil pipe is subjected to a heating boronizing treatment, and after cooling, an oil pipe having a boronized layer on the inner surface is obtained.
[0026] In the solid boronizing method for the oil pipe as described above, preferably, in step S3, the outer surface of the oil pipe is wrapped with a deoxidizer and metal ceramic balls in sequence, and then the metal ceramic balls are sealed with quartz sand powder.
[0027] In the solid boronizing method of the oil pipe as described above, preferably, the thickness of the metal ceramic ball layer is 100-150 mm, the particle size of the metal ceramic ball is 1-2 mm, the particle size of the quartz sand powder is 300-350 mesh, and after the quartz sand powder is sealed, the thickness of the quartz sand powder layer is 60-100 mm.
[0028] In the solid boronizing method for the oil pipe as described above, preferably, in step S4, the heating boronizing treatment includes: heating the sealed oil pipe to 660-700°C, keeping it warm for 10-20 minutes, then heating it to 760-800°C, keeping it warm for 5-15 minutes, continuing to heat it to 810-840°C, keeping it warm for 15-25 minutes, then heating it to 850-950°C and keeping it warm for 4-6 hours, and finally cooling it to room temperature to complete the heating treatment.
[0029] In the solid boronizing method of the oil pipe as described above, preferably, the oil pipe is made of ordinary alloy steel or high alloy steel;
[0030] In the ordinary alloy steel, the total content of alloying elements is ≤5wt%,
[0031] In the high alloy steel, the total content of alloying elements is >5wt%.
[0032] (III) Beneficial effects
[0033] The composite boronizing agent of the present invention uses triethanolamine borate as a dispersant. In the solid boronizing process, the triethanolamine borate can wrap the boron supply agent and the catalyst, and then react with the metal oxide on the inner surface of the oil pipe to form a combination. The combination is further decomposed to generate water and hydrogen fluoride. The water and the hydrogen fluoride form hydrofluoric acid and remove impurities such as the metal oxide on the inner surface of the oil pipe, thereby achieving a secondary rust removal effect and improving the boronizing effect and the quality of the boronized layer.
[0034] During the boronizing process, triethanolamine borate can also form a protective film on the inner surface of the oil pipe to prevent the workpiece from oxidizing and help the boronizing process.
[0035] In addition, the protective film formed by triethanolamine borate on the inner surface of the oil pipe can also prevent carbon atoms from entering the oil pipe, avoid carburization, promote boronization, and thus solve the problem of only carburizing but not boronizing in the existing boronizing process, improve the bonding strength of the boronized layer, and avoid the boronized layer from falling off.
[0036] In addition, the composite boronizing agent of the present invention also includes graphite. Under the joint action of triethanolamine borate and graphite in the boronizing agent, the boronizing agent can be prevented from agglomerating and adhering to the inner wall of the oil pipe after the boronizing treatment, and the uniformity of the boronizing can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 is a microstructure diagram of the boronized layer on the inner surface of the oil pipe in Example 1;
[0038] Figure 2 is a microstructure diagram of the boronized layer on the inner surface of the oil pipe in Comparative Example 3;
[0039] Figure 3 is a microstructure diagram of the boronized layer on the inner surface of the oil pipe in Example 2;
[0040] Figure 4 The metallographic structure diagram of the alloy steel substrate of the oil pipe connected to the boronized layer in Example 2;
[0041] Figure 5 is a microstructure diagram of the boronized layer on the inner surface of the oil pipe in Example 3;
[0042] Figure 6 is a microstructure diagram of the boronized layer on the inner surface of the oil pipe in Example 4;
[0043] Figure 7 The microstructure diagram of the boronized layer on the inner surface of the oil pipe in Example 5 and the metallographic structure diagram of the alloy steel substrate of the oil pipe connected to the boronized layer;
[0044] Figure 8 This is the microstructure of the boronized layer in the control product;
[0045] Fig. 9 This is the metallographic structure of the alloy steel matrix of the oil pipe connected to the boronized layer in the reference product;
[0046] Fig.10 The oil pipe sample prepared in Example 2 is immersed in a 25wt% hydrochloric acid solution, and the morphological changes of the sample are observed at different time points;
[0047] Fig.11 The morphological changes of the reference tubing sample observed at different time points were shown when it was immersed in a 25wt% hydrochloric acid solution;
[0048] Fig.12The oil pipe sample prepared in Example 2 is immersed in a 10wt% NaCl solution, and the morphological changes of the sample are observed at different time points;
[0049] Fig.13 The morphological changes of the reference tubing sample observed at different time points were shown when the sample was immersed in a 10wt% NaCl solution;
[0050] Fig.14 The oil pipe sample prepared in Example 2 is immersed in a 25wt% HNO3 solution, and the morphological changes of the sample observed at different time points;
[0051] Fig.15 The morphological changes of the reference tubing sample observed at different time points were shown when it was immersed in a 25wt% HNO3 solution. DETAILED DESCRIPTION
[0052] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below in conjunction with specific implementation methods.
[0053] The present invention provides a composite boronizing agent, comprising a boronizing agent and graphite. In which, according to mass percentage, the graphite accounts for 10-14% of the mass of the boronizing agent. The boronizing agent comprises the following raw materials in mass percentage: a boronizing agent: 10-15%, a catalyst: 12-20%, an activator: 8-10%, a dispersant: 4-6%, a filler: 50-55%, and a flow aid: 8-12%. The dispersant used in the present invention is triethanolamine borate (TEAB, chemical formula C6H 12 BNO3).
[0054] In the present invention, the boron supplying agent is preferably boric anhydride or boron carbide. The boron supplying agent in the existing boronizing agent is generally boron carbide, and the amount of boron carbide added can reach about 50% of the mass of the boronizing agent. After long-term research, the researchers of the present invention found that a higher content of boron carbide is added to the boronizing agent of the prior art, but boron carbide can only supply boron at high temperatures. In addition to boron carbide, the present invention can also use boric anhydride as a boron supplying agent. The boron supply temperature of boric anhydride is lower than that of boron carbide, which can play a role in continuous boron supply during the boronizing process. The boronizing agent of the present invention is preferably used when the boronizing treatment temperature is high in the boronizing process, such as above 900°C, and is preferably used when the boronizing treatment temperature is low in the boronizing process, such as 850-900°C.
[0055] The above-mentioned catalyst preferably includes potassium fluoroborate, sodium fluoride and potassium fluoride. Wherein, potassium fluoroborate accounts for 5-10% of the total mass of the boronizing agent, sodium fluoride accounts for 5-6% of the total mass of the boronizing agent, and potassium fluoride accounts for 2-4% of the total mass of the boronizing agent. In the present invention, the addition amount of the catalyst needs to be strictly controlled at 12-20%. If the addition amount exceeds 20%, there will be too many holes in the boronizing layer, and the boronizing agent will be agglomerated, affecting the quality of the boronizing layer.
[0056] The above-mentioned activator preferably includes silicon dioxide and activated carbon. Wherein, silicon dioxide accounts for 5-7% of the total mass of the boronizing agent, and activated carbon accounts for 2-4% of the total mass of the boronizing agent. The activator of the present invention has a two-way effect, which can be used as an oxidant and, because of its high melting point, can also be used as a dispersant. Wherein, as a dispersant, it is specifically manifested in dispersing the catalyst, being able to control the reaction activity of the catalyst, slowing down the decomposition rate of potassium fluoroborate in the catalyst, and improving the effect of boronizing.
[0057] The bidirectional action of the activator in the present invention is as follows:
[0058] Potassium fluoroborate in the catalyst undergoes the following decomposition reaction at high temperature:
[0059]
[0060] Taking boron carbide as a boron supply agent as an example, the boron supply agent of the present invention reacts with BF3 and KF produced by the decomposition of potassium fluoroborate during the boronizing process to achieve boronizing:
[0061]
[0062] ④
[0063] It should be noted that oxygen is involved in the above-mentioned boronizing reaction ②, reaction ③ and reaction ④, and the oxygen involved in the reaction all comes from the air naturally carried during the wrapping and sealing process of the oil pipe.
[0064] The present invention selects activated carbon and silicon dioxide as activators. Under high temperature conditions, silicon dioxide and activated carbon can undergo the following reaction:
[0065] ⑤
[0066] The above reaction ⑤ can generate carbon monoxide, which can disperse and adjust the concentration of boron fluoride during the boriding process, play the role of a dispersant, avoid excessive boron fluoride concentration, and improve the boriding effect.
[0067] Silica and activated carbon have more porous structures, so they can carry oxygen and act as oxidants. In addition, when the oxygen content is high, activated carbon can also react with excess oxygen to generate carbon monoxide or carbon dioxide gas, which not only acts as a reducing agent, but also can disperse the concentration of boron fluoride.
[0068] In the present invention, potassium fluoroborate can achieve boronization by diffusing boron in the form of gas after decomposition at high temperature, and the boron supply agent can also achieve boronization by contact diffusion.
[0069] Preferably, the filler of the present invention comprises aluminum oxide and / or silicon carbide. Specifically, it is necessary to select white aluminum oxide with high purity, such as white aluminum oxide with a purity of 99.99% or more, and the particle size of the aluminum oxide is 0.1-0.2 mm. Silicon carbide is green silicon carbide, and its particle size can be 140-160 mesh.
[0070] Preferably, the flow aid preferably includes charcoal powder and graphite powder. The charcoal powder accounts for 3-5% of the total mass of the boriding agent, the graphite powder accounts for 4-8% of the total mass of the boriding agent, and the particle size of the graphite powder is 140-160 mesh. In the present invention, the addition of the flow aid can prevent the boriding agent from agglomerating before use.
[0071] Further preferably, the particle size of the graphite mixed with the boronizing agent is 30-50 mesh.
[0072] The present invention also provides a solid boronizing method for an oil pipe, comprising the following steps:
[0073] S1: Clean the inner surface of the oil pipe.
[0074] S2: The boronizing agent in the composite boronizing agent is mixed with graphite to obtain a composite boronizing agent, and then the composite boronizing agent is loaded into the oil pipe so that the composite boronizing agent contacts the inner surface of the oil pipe.
[0075] S3: Sealing the oil pipe filled with composite boronizing agent.
[0076] S4: The sealed oil pipe is subjected to a heating boronizing treatment, and after cooling, an oil pipe having a boronized layer on the inner surface is obtained.
[0077] In the above step S1, the inner surface of the oil pipe is subjected to rust removal. After the rust removal, the oil pipe needs to be dried to remove moisture therein.
[0078] The composite boronizing agent of the present invention uses triethanolamine borate as a dispersant. During the heat treatment process of the boronizing process, the triethanolamine borate can wrap the boron supply agent and the catalyst, and then react with the metal oxide on the inner surface of the oil pipe to form a combination. The combination decomposes to generate water and hydrogen fluoride. Water and hydrogen fluoride can form hydrofluoric acid, which removes impurities such as metal oxides on the inner surface of the oil pipe, achieves a secondary rust removal effect, and can improve the quality of the boronized layer.
[0079] During the boronizing process, triethanolamine borate can also form a protective film on the inner surface of the oil pipe to prevent the workpiece from oxidizing and help the boronizing process.
[0080] Since ordinary alloy steel workpieces or high alloy steel oil pipes contain carbon elements, the flow aid includes graphite powder, and the boriding agent is also mixed with graphite, the carbon content will gradually increase during the boriding process, and a large number of carburized layers will be produced on the inner surface of the oil pipe during the boriding process, which will prevent the entry of boron atoms, form a large number of loose layers and holes, and make the boriding agent unusable, resulting in the phenomenon of only carburizing but not boriding. Triethanolamine borate can form a protective film on the surface of the workpiece to prevent carbon atoms from entering the workpiece, reduce carburization, promote boriding, and thus solve the problem of only carburizing but not boriding in the existing boriding process, improve the bonding strength of the boriding layer, and avoid the boriding layer from falling off.
[0081] The present invention also mixes the boronizing agent with graphite and loads it into the inside of the oil pipe to carry out boronizing treatment. Under the joint action of triethanolamine borate and graphite, the boronizing agent can be prevented from caking and adhering to the inner wall of the oil pipe, and the uniformity of boronizing can also be improved. If triethanolamine borate is not added, even if the boronizing agent is used after drying, there will be a caking problem to varying degrees, the boronizing agent is easy to get wet, and after the boronizing treatment, the boronizing agent is stuck on the surface of the workpiece and is difficult to clean. If graphite is not added, for long oil pipes, especially long oil pipes with a length of ≥9.7m, the problem of uneven boronizing of the boronizing agent after the boronizing treatment will be more obvious due to the long length of the oil pipe. In addition, if graphite is not added, for long oil pipes with a length of ≥9.7m, the boronizing agent does not have obvious caking, but is still difficult to completely remove from the inner wall of the oil pipe, and the uniformity of boronizing will also be affected.
[0082] In the above step S2, before the composite boronizing agent is loaded into the oil pipe, in order to avoid boronization at the oil pipe thread and change the mechanical properties of the thread, it is also necessary to apply a high temperature resistant anti-seepage agent at the oil pipe thread. Moreover, before the composite boronizing agent is loaded into the oil pipe, the composite boronizing agent can also be dried to remove the moisture therein, the drying temperature is ≤120°C, and the drying time is 15-25min.
[0083] In the above step S3, the outer surface of the oil pipe is wrapped with a deoxidizer and a metal ceramic ball in sequence, and then the metal ceramic ball is sealed with quartz sand powder to reduce the influence of air on boronization. The particle size of the metal ceramic ball is 1-2 mm, the thickness of the metal ceramic ball layer formed after the metal ceramic ball is wrapped is 100-150 mm, preferably 120 mm, the particle size of the quartz sand powder is 300-350 mesh, preferably 325 mesh, and after the quartz sand powder is sealed, the thickness of the quartz sand powder layer is 60-100 mm, preferably 80 mm.
[0084] In addition, the sealing process in step S3 can also be achieved by placing the entire oil pipe filled with the composite boronizing agent in the sealing device.
[0085] In the above step S4, the heating boriding treatment includes: placing the sealed oil pipe in a heating device for heating treatment, so that the boron element in the boriding agent diffuses to the inner surface of the oil pipe to form a boriding layer. The heating treatment specifically includes: heating the oil pipe to 660-700°C, keeping it warm for 10-20 minutes, then heating it to 760-800°C, keeping it warm for 5-15 minutes, continuing to heat it to 810-840°C, keeping it warm for 15-25 minutes, then heating it to 850-950°C and keeping it warm for 4-6 hours, and finally cooling it to room temperature to complete the heating treatment. Post-processing the oil pipe after the heat treatment can obtain an oil pipe with borided inner surface.
[0086] If the boron supply agent in the boronizing agent of step S4 is boric anhydride, the heating treatment in step A5 specifically includes: heating to 660-700°C, keeping warm for 10-20 minutes, then heating to 760-800°C, keeping warm for 5-15 minutes, continuing to heat to 810-840°C, keeping warm for 15-25 minutes, then heating to 850-900°C and keeping warm for 4-6 hours, and finally cooling the furnace to room temperature to complete the heating treatment.
[0087] If the boron supply agent in the boronizing agent of step S4 is boron carbide, the heating treatment in step A5 specifically includes: heating to 660-700°C, keeping warm for 10-20 minutes, then heating to 760-800°C, keeping warm for 5-15 minutes, continuing to heat to 810-840°C, keeping warm for 15-25 minutes, then heating to greater than 900°C and less than or equal to 950°C, continuing to keep warm for 4-6 hours, and finally cooling the furnace to room temperature to complete the heating treatment.
[0088] It should be noted that the solid boronizing method of the oil pipe of the present invention can be applied to various oil pipes, or similar tubular articles and other articles, and is not limited to oil pipes with a length of ≥9.7m. The oil pipe of the present invention is prepared by ordinary alloy steel or high alloy steel, wherein the total content of alloy elements in the ordinary alloy steel is ≤5wt%, and the total content of alloy elements in the high alloy steel is >5wt%.
[0089] The preparation method of the boronizing agent used in the present invention comprises the following steps:
[0090] A1: Part of the catalyst and part of the activator are mixed uniformly to obtain a mixture, and then triethanolamine borate is dissolved in an organic solvent to obtain a triethanolamine borate solution. Triethanolamine borate is viscous and colloid, and it is difficult to directly and uniformly mix with other components. Therefore, in the present invention, triethanolamine borate is dissolved in an organic solvent and then mixed with other components.
[0091] A2: The triethanolamine borate solution is mixed evenly with the mixture, and the mixture is dried and crushed to obtain a first powder.
[0092] A3: Add the boron supply agent, filler, flow aid, catalyst of the remaining components and activator of the remaining components to the first powder and mix them evenly to obtain the boronizing agent.
[0093] Since the content of triethanolamine borate in the boriding agent of the present invention is relatively low, it is difficult to uniformly mix with other components with higher content. Therefore, in the process of preparing the boriding agent, part of the catalyst and part of the activator are mixed with triethanolamine borate to obtain powder particles containing triethanolamine borate. These powder particles are mixed with other ingredients to improve the mixing uniformity of each component, and the powder particles adsorbed with triethanolamine borate can encapsulate the boron supply agent and the catalyst in the boriding agent, which is beneficial to heat transfer and mass transfer in the boriding heat treatment process and improves the secondary rust removal and boriding effects.
[0094] The boronizing agent includes, by mass percentage, 10-15% of a boron supply agent, 12-20% of a catalyst, 8-10% of an activator, 50-55% of a filler, 8-12% of a flow aid and 4-6% of triethanolamine borate.
[0095] Preferably, in step A1, the catalyst in the mixture accounts for 2-4% of the mass of the boriding agent, and the activator in the mixture accounts for 2-4% of the mass of the boriding agent.
[0096] Preferably, in step A2, the purpose of drying is to remove organic solvent and moisture, the drying temperature is ≤100° C., and the particle size of the first powder is 140-160 mesh.
[0097] In order to further clarify the scheme of the present invention and its technical advancement, the following is a description in conjunction with specific embodiments and technical effects.
[0098] Example 1
[0099] This embodiment provides a solid boronizing method for an oil pipe, comprising the following steps:
[0100] S1: The inner surface of a high alloy steel oil pipe with a length of 9.7 m was subjected to rust removal treatment.
[0101] S2: Dry the boronizing agent at a temperature of 120°C for 20 minutes. Apply a high temperature resistant anti-seepage agent to the threads of the oil pipe. Mix the boronizing agent with graphite to obtain a composite boronizing agent, and then load the composite boronizing agent into the interior of an oil pipe with a length of 9.7m so that the composite boronizing agent contacts the inner surface of the oil pipe. In the composite boronizing agent, graphite accounts for 12% of the mass of the boronizing agent. The boronizing agent includes the following raw materials in mass percentage: boron carbide: 12%, potassium fluoroborate: 5.5%, sodium fluoride: 5.5%, potassium fluoride: 3%, silicon dioxide: 5%, activated carbon: 4%, triethanolamine borate: 5%, aluminum oxide: 51%, charcoal powder: 5%, graphite powder: 4%.
[0102] S3: Wrap the deoxidizer and the metal ceramic ball with a diameter of 1 mm on the outside of the oil pipe in turn, the thickness of the metal ceramic ball layer is 120 mm, and then seal the metal ceramic ball with 325 mesh quartz sand powder, and the sealing thickness is 80 mm.
[0103] S4: Place the sealed oil pipe in a heating furnace, raise the temperature to 680°C, keep it warm for 15 minutes, then raise the temperature to 780°C, keep it warm for 10 minutes, continue to raise the temperature to 820°C, keep it warm for 20 minutes, then raise the temperature to 950°C and keep it warm for 5 hours, and finally cool the furnace to room temperature.
[0104] S5: performing post-processing on the oil pipe after the heating treatment to obtain the oil pipe with boronized inner surface.
[0105] In this embodiment, the preparation method of the boronizing agent is as follows:
[0106] A1: 5.5% potassium fluoroborate, 5.5% sodium fluoride and 3% potassium fluoride are mixed evenly to obtain a catalyst, and 5% silicon dioxide and 4% activated carbon are mixed evenly to obtain an activator. Part of the catalyst and part of the activator are mixed evenly to obtain a mixture, and then 5% triethanolamine borate is dissolved in an organic solvent to obtain a triethanolamine borate solution.
[0107] A2: The triethanolamine borate solution and the mixture are uniformly mixed, dried at 80° C., and crushed to obtain a first powder with a particle size of 150 mesh.
[0108] A3: 12% of boron carbide, 51% of aluminum oxide, 5% of charcoal powder, 4% of graphite powder, the remaining catalyst and the remaining activator are added to the first powder and mixed evenly to obtain a boronizing agent.
[0109] In step A1, the catalyst in the mixture accounts for 3% of the mass of the boriding agent, and the activator in the mixture accounts for 3% of the mass of the boriding agent.
[0110] The percentages in the embodiments of the present invention and the comparative examples are all by mass percentages.
[0111] Example 2
[0112] This embodiment provides a solid boronizing method for an oil pipe, comprising the following steps:
[0113] S1: The inner surface of a high alloy steel oil pipe with a length of 10.3 m is subjected to rust removal treatment.
[0114] S2: Dry the boronizing agent at a temperature of 100°C for 25 minutes. Apply a high temperature resistant anti-seepage agent to the threads of the oil pipe. Mix the boronizing agent with graphite to obtain a composite boronizing agent, and then load the composite boronizing agent into the interior of an oil pipe with a length of 10.3m so that the composite boronizing agent contacts the inner surface of the oil pipe. In the composite boronizing agent, graphite accounts for 10% of the mass of the boronizing agent. The boronizing agent includes the following raw materials in mass percentage: boron carbide: 10%, potassium fluoroborate: 5%, sodium fluoride: 5%, potassium fluoride: 2%, silicon dioxide: 5%, activated carbon: 3%, triethanolamine borate: 6%, aluminum oxide: 55%, charcoal powder: 4%, graphite powder: 5%.
[0115] S3: Wrap the deoxidizer and the metal ceramic ball with a diameter of 2 mm on the outside of the oil pipe in sequence, the thickness of the metal ceramic ball layer is 100 mm, and then seal the metal ceramic ball with 300 mesh quartz sand powder, the sealing thickness is 100 mm.
[0116] S4: Place the sealed oil pipe in a heating furnace, raise the temperature to 660°C, keep it warm for 20 minutes, then raise the temperature to 760°C, keep it warm for 15 minutes, continue to raise the temperature to 840°C, keep it warm for 25 minutes, then raise the temperature to 910°C and keep it warm for 4 hours, and finally cool the furnace to room temperature.
[0117] S5: performing post-processing on the oil pipe after the heating treatment to obtain the oil pipe with boronized inner surface.
[0118] In this embodiment, the preparation method of the boronizing agent is as follows:
[0119] A1: 5% potassium fluoroborate, 5% sodium fluoride and 2% potassium fluoride are mixed evenly to obtain a catalyst, and 5% silicon dioxide and 3% activated carbon are mixed evenly to obtain an activator. Part of the catalyst and part of the activator are mixed evenly to obtain a mixture, and then 6% triethanolamine borate is dissolved in an organic solvent to obtain a triethanolamine borate solution.
[0120] A2: The triethanolamine borate solution and the mixture are uniformly mixed, dried at 100° C., and crushed to obtain a first powder with a particle size of 140 mesh.
[0121] A3: 10% of boron carbide, 55% of aluminum oxide, 4% of charcoal powder, 5% of graphite powder, the remaining catalyst and the remaining activator are added to the first powder and mixed evenly to obtain a boronizing agent.
[0122] In step A1, the catalyst in the mixture accounts for 2% of the mass of the boriding agent, and the activator in the mixture accounts for 4% of the mass of the boriding agent.
[0123] Example 3
[0124] This embodiment provides a solid boronizing method for an oil pipe, comprising the following steps:
[0125] S1: The inner surface of a high alloy steel oil pipe with a length of 9.7 m was subjected to rust removal treatment.
[0126] S2: Dry the boronizing agent at a temperature of 120°C for 20 minutes. Apply a high temperature resistant anti-seepage agent to the threads of the oil pipe. Mix the boronizing agent with graphite to obtain a composite boronizing agent, and then load the composite boronizing agent into the interior of an oil pipe with a length of 9.7m so that the composite boronizing agent contacts the inner surface of the oil pipe. In the composite boronizing agent, graphite accounts for 14% of the mass of the boronizing agent. The boronizing agent includes the following raw materials in mass percentage: boric anhydride: 15%, potassium fluoroborate: 5%, sodium fluoride: 6%, potassium fluoride: 2%, silicon dioxide: 7%, activated carbon: 3%, triethanolamine borate: 4%, aluminum oxide: 25%, silicon carbide: 25%, charcoal powder: 3%, graphite powder: 5%.
[0127] S3: Wrap the deoxidizer and the metal ceramic ball with a diameter of 1.5 mm on the outside of the oil pipe in sequence, the thickness of the metal ceramic ball layer is 150 mm, and then seal the metal ceramic ball with 350 mesh quartz sand powder, and the sealing thickness is 60 mm.
[0128] S4: Place the sealed oil pipe in a heating furnace, raise the temperature to 700°C, keep it warm for 10 minutes, then raise the temperature to 800°C, keep it warm for 5 minutes, continue to raise the temperature to 810°C, keep it warm for 15 minutes, then raise the temperature to 850°C and keep it warm for 4 hours, and finally cool the furnace to room temperature.
[0129] S5: performing post-processing on the oil pipe after the heating treatment to obtain the oil pipe with boronized inner surface.
[0130] In this embodiment, the preparation method of the boronizing agent is as follows:
[0131] A1: 5% potassium fluoroborate, 6% sodium fluoride and 2% potassium fluoride are mixed evenly to obtain a catalyst, and 7% silicon dioxide and 3% activated carbon are mixed evenly to obtain an activator. Part of the catalyst and part of the activator are mixed evenly to obtain a mixture, and then 4% triethanolamine borate is dissolved in an organic solvent to obtain a triethanolamine borate solution.
[0132] A2: The triethanolamine borate solution and the mixture are uniformly mixed, and then dried and crushed to obtain a first powder with a particle size of 160 mesh.
[0133] A3: 15% of boric anhydride, 25% of aluminum oxide, 25% of silicon carbide, 3% of charcoal powder, 5% of graphite powder, the remaining catalyst and the remaining activator are added to the first powder and mixed evenly to obtain a boronizing agent.
[0134] In step A1, the catalyst in the mixture accounts for 4% of the mass of the boriding agent, and the activator in the mixture accounts for 2% of the mass of the boriding agent.
[0135] Example 4
[0136] This embodiment provides a method for solid boronizing of an oil pipe, comprising the following steps:
[0137] S1: The inner surface of a common alloy steel oil pipe with a length of 11m is subjected to rust removal treatment.
[0138] S2: Dry the boronizing agent at a temperature of 120°C for 20 minutes. Apply a high temperature resistant anti-seepage agent to the threads of the oil pipe. Mix the boronizing agent with graphite to obtain a composite boronizing agent, and then load the composite boronizing agent into the interior of an oil pipe with a length of 11m so that the composite boronizing agent contacts the inner surface of the oil pipe. In the composite boronizing agent, graphite accounts for 12% of the mass of the boronizing agent. The boronizing agent includes the following raw materials in mass percentage: boron carbide: 10%, potassium fluoroborate: 10%, sodium fluoride: 6%, potassium fluoride: 4%, silicon dioxide: 6%, activated carbon: 2%, triethanolamine borate: 4%, silicon carbide: 50%, charcoal powder: 3%, graphite powder: 5%.
[0139] S3: Wrap the deoxidizer and the metal ceramic ball with a diameter of 1.2 mm on the outside of the oil pipe in turn, the thickness of the metal ceramic ball layer is 120 mm, and then seal the metal ceramic ball with 325 mesh quartz sand powder, and the sealing thickness is 80 mm.
[0140] S4: Place the sealed oil pipe in a heating furnace, raise the temperature to 680°C, keep it warm for 15 minutes, then raise the temperature to 780°C, keep it warm for 10 minutes, continue to raise the temperature to 830°C, keep it warm for 20 minutes, then raise the temperature to 920°C and keep it warm for 5 hours, and finally cool the furnace to room temperature.
[0141] S5: performing post-processing on the oil pipe after the heating treatment to obtain the oil pipe with boronized inner surface.
[0142] In this embodiment, the preparation method of the boronizing agent is as follows:
[0143] A1: 10% potassium fluoroborate, 6% sodium fluoride and 4% potassium fluoride are mixed evenly to obtain a catalyst, and 6% silicon dioxide and 2% activated carbon are mixed evenly to obtain an activator. Part of the catalyst and part of the activator are mixed evenly to obtain a mixture, and then 4% triethanolamine borate is dissolved in an organic solvent to obtain a triethanolamine borate solution.
[0144] A2: The triethanolamine borate solution and the mixture are uniformly mixed, dried at 60° C., and crushed to obtain a first powder with a particle size of 150 mesh.
[0145] A3: 10% boron carbide, 50% silicon carbide, 3% charcoal powder, 5% graphite powder, the remaining catalyst and the remaining activator are added to the first powder and mixed evenly to obtain a boronizing agent.
[0146] In step A1, the catalyst in the mixture accounts for 3% of the mass of the boriding agent, and the activator in the mixture accounts for 3% of the mass of the boriding agent.
[0147] Example 5
[0148] This embodiment provides a method for solid boronizing of an oil pipe, comprising the following steps:
[0149] S1: The inner surface of a 9.7m long common alloy steel oil pipe was subjected to rust removal treatment.
[0150] S2: Dry the boronizing agent at a temperature of 120°C for 20 minutes. Apply a high temperature resistant anti-seepage agent to the threads of the oil pipe. Mix the boronizing agent with graphite to obtain a composite boronizing agent, and then load the composite boronizing agent into the interior of an oil pipe with a length of 9.7m so that the composite boronizing agent contacts the inner surface of the oil pipe. In the composite boronizing agent, graphite accounts for 10% of the mass of the boronizing agent. The boronizing agent includes the following raw materials in mass percentage: boric anhydride: 10%, potassium fluoroborate: 5%, sodium fluoride: 5%, potassium fluoride: 2%, silicon dioxide: 6%, activated carbon: 3%, triethanolamine borate: 5%, silicon carbide: 52%, charcoal powder: 4%, graphite powder: 8%.
[0151] S3: Wrap the deoxidizer and the metal ceramic ball with a diameter of 1.8 mm on the outside of the oil pipe in sequence, the thickness of the metal ceramic ball layer is 120 mm, and then seal the metal ceramic ball with 325 mesh quartz sand powder, the sealing thickness is 80 mm.
[0152] S4: Place the sealed oil pipe in a heating furnace, raise the temperature to 680°C, keep it warm for 15 minutes, then raise the temperature to 780°C, keep it warm for 10 minutes, continue to raise the temperature to 825°C, keep it warm for 20 minutes, then raise the temperature to 900°C and keep it warm for 5 hours, and finally cool the furnace to room temperature.
[0153] S5: performing post-processing on the oil pipe after the heating treatment to obtain the oil pipe with boronized inner surface.
[0154] In this embodiment, the preparation method of the boronizing agent is as follows:
[0155] A1: 5% potassium fluoroborate, 5% sodium fluoride and 2% potassium fluoride are mixed evenly to obtain a catalyst, and 6% silicon dioxide and 3% activated carbon are mixed evenly to obtain an activator. Part of the catalyst and part of the activator are mixed evenly to obtain a mixture, and then 5% triethanolamine borate is dissolved in an organic solvent to obtain a triethanolamine borate solution.
[0156] A2: The triethanolamine borate solution and the mixture are uniformly mixed, dried at 80° C., and crushed to obtain a first powder with a particle size of 150 mesh.
[0157] A3: 10% of boric anhydride, 51% of silicon carbide, 4% of charcoal powder, 8% of graphite powder, the remaining catalyst and the remaining activator are added to the first powder and mixed evenly to obtain a boronizing agent.
[0158] In step A1, the catalyst in the mixture accounts for 3% of the mass of the boriding agent, and the activator in the mixture accounts for 3% of the mass of the boriding agent.
[0159] Comparative Example 1
[0160] The difference between this comparative example and Example 1 is that the content of triethanolamine borate in the boronizing agent is 0. In this comparative example, the preparation method of the boronizing agent is: uniformly mixing the raw material components of the boronizing agent of various contents, drying and crushing to obtain the boronizing agent.
[0161] Comparative Example 2
[0162] The difference between this comparative example and Example 1 is that the content of the catalyst in the boronizing agent is 25%.
[0163] Comparative Example 3
[0164] The difference between this comparative example and Example 1 is that in step S2, the content of graphite in the composite boronizing agent is 0.
[0165] Comparative Example 4
[0166] The difference between this comparative example and Example 4 is that the content of triethanolamine borate in the boronizing agent is 0. In this comparative example, the preparation method of the boronizing agent is: uniformly mixing the raw material components of the boronizing agent of various contents, drying and crushing to obtain the boronizing agent.
[0167] The performance tests were conducted on the oil pipes with boronized inner surfaces prepared in Examples 1-5 and Comparative Examples 1-4. Specifically, the thickness of the boronized layer on the inner surface of the oil pipe, the maximum microhardness corresponding to a certain depth in the boronized layer, the tensile strength, yield strength, elongation, and breakpoint shrinkage of the inner surface of the oil pipe were measured. The results are shown in Table 1.
[0168] Table 1 Statistical table of performance test results of the inner surface boronized oil pipes of Examples 1-5 and Comparative Examples 1-4
[0169]
[0170] As shown in Table 1, the boriding layers of Examples 1-5 have high thickness, hardness and good mechanical properties, and the hardness and related mechanical properties of the boriding layers are much higher than the hardness and mechanical properties of the original ordinary alloy steel long oil pipe matrix / high alloy steel long oil pipe matrix. In Comparative Examples 1 and 4, since no triethanolamine borate was added, the boriding layers prepared therefrom are thinner in thickness, lower in hardness and poorer in mechanical properties. In Comparative Example 2, due to excessive addition of catalyst, the thickness, hardness and mechanical properties of the boriding layers prepared therefrom are significantly reduced compared to Examples 1-3.
[0171] The inner surface of the oil pipes of Examples 1-5 and Comparative Examples 1-4 was cut and polished, and the microstructure of the interface between the boronized layer and the substrate was observed using a scanning electron microscope. It was observed that there were almost no cracks and holes between the boronized layer and the substrate of Examples 1-5, and there was no delamination phenomenon, indicating that the boronized layer and the substrate had a high degree of bonding. Some cracks and holes were observed between the boronized layer and the substrate of Comparative Examples 1, 2 and 4, among which the cracks and holes between the boronized layer and the substrate of Comparative Examples 1 and 4 were more than those of Comparative Example 2, indicating that the bonding between the boronized layer and the substrate in Comparative Examples 1 and 2 was low, and there was a risk of the boronized layer falling off.
[0172] In addition, after the inner surfaces of the oil pipes of Examples 1-5 and Comparative Examples 1-4 were subjected to boriding treatment, the agglomeration of the boriding agent in the inner surfaces of the oil pipes was observed. It was observed that the boriding agent of Examples 1-5 did not agglomerate, and the boriding agent and the oil pipe could be separated relatively easily. The boriding agents in Comparative Examples 1-4 all agglomerated, and due to the long length of the oil pipe, it was difficult to remove all the residual boriding agent from the inner wall of the oil pipe, and the uniformity of the boriding in Comparative Example 3 was also low.
[0173] Figure 1 as well as Figure 2 The microstructures of the boronized layer on the inner surface of the oil pipe in Example 1 and Comparative Example 3 are shown in FIG. Figure 1 as well as Figure 2 It can be clearly seen that the thickness of the boronized layer in Example 1 is relatively high, while the thickness of the boronized layer in Comparative Example 3 is relatively low. Figure 5 and Figure 6 They are respectively the microstructure diagrams of the boronized layer on the inner surface of the oil pipe in Example 3 and Example 4, Figure 7 The microstructure of the boronized layer on the inner surface of the oil pipe in Example 5 and the metallographic structure of the oil pipe alloy steel matrix connected to the boronized layer are shown. Figure 5 , Figure 6 as well as Figure 7 It can be seen that the quality of the boronized layers in Examples 3, 4 and 5 is good. Figure 7 It can be seen that after the boriding treatment in Example 5, the boriding layer has no effect on the alloy steel substrate.
[0174] The best boronized oil pipe in foreign countries is used as a reference product. The length and material of the reference oil pipe are the same as those of the high alloy steel oil pipe in Example 2. The boronizing effect and corrosion resistance of the boronized oil pipe in Example 2 and the reference product are compared:
[0175] ① Boriding effect:
[0176] Figure 3 is the microstructure diagram of the boronized layer in Example 2, Figure 4 This is the metallographic structure diagram of the alloy steel substrate connected to the boronized layer in Example 2. Figure 8 is the microstructure of the boronized layer in the control sample. Fig. 9 This is the metallographic structure diagram of the alloy steel matrix connected to the boronized layer in the reference sample.
[0177] pass Figure 3 as well as Figure 8 It can be seen from the comparison that the thickness of the boronized layer and the uniformity of the boronized layer in Example 2 are significantly higher than those in the control.
[0178] pass Figure 4 as well as Fig. 9 It can be seen from the comparison that after the boronizing treatment in Example 2, the boronizing layer has no effect on the alloy steel matrix. The lattice of the alloy steel matrix in Example 2 is refined, the crystals are evenly distributed, and the texture is compact, indicating that the boronizing method of Example 2 can maintain the mechanical properties of the alloy steel oil pipe itself. The grains in the reference product are relatively coarse and irregular, indicating that the boronizing layer of the reference product has an impact on the alloy steel matrix, making its grains larger.
[0179] ②Corrosion resistance:
[0180] 1. Hydrochloric acid corrosion resistance:
[0181] A sample with a boronized layer was cut from the boronized oil pipe prepared in Example 2, and recorded as Sample 1. Similarly, a sample 2 with a boronized layer of the same size was cut from the boronized oil pipe of the reference product, and the corrosion resistance of Samples 1 and 2 was tested. Specifically, at 30°C, Samples 1 and 2 were immersed in a hydrochloric acid solution with a mass concentration of 25%, and the morphological changes of Samples 1 and 2 were recorded on the first day, the first week, the second week, the third week, and the fourth week, respectively, to obtain Fig.10 as well as Fig.11 .
[0182] pass Fig.10 It can be seen that on the first day, bubbles were generated in the hydrochloric acid solution and the solution turned slightly yellow. In the first week, the hydrochloric acid solution turned light green. In the second week, the degree of corrosion of Sample 1 increased. After weighing, the mass loss of Sample 1 at this time was 12.88% compared with that before immersion. In the third week, it was observed that the boronized layer of Sample 1 was still good. After weighing, the mass loss of Sample 1 at this time was 16.56% compared with that before immersion. In the fourth week, it was observed that the edge of the boronized layer of Sample 1 was damaged. After weighing, the mass loss of Sample 1 at this time was 21.29% compared with that before immersion.
[0183] pass Fig.11 It can be seen that on the first day, a large number of bubbles were generated in the hydrochloric acid solution and the solution turned yellow. In the first week, the hydrochloric acid solution turned green. In the second week, the corrosion of sample 2 was serious. After weighing, the mass loss of sample 2 at this time was 18.87% compared with that before immersion. In the third week, it was observed that the boronized layer of sample 2 was damaged. After weighing, the mass loss of sample 2 at this time was 24.11% compared with that before immersion. In the fourth week, it was observed that the boronized layer of sample 2 had completely fallen off. After weighing, the mass loss of sample 2 at this time was 31.63% compared with that before immersion.
[0184] 2. Salt solution corrosion resistance:
[0185] A sample with a boronized layer was cut from the boronized oil pipe prepared in Example 2, and recorded as Sample 3. Similarly, a sample 4 with a boronized layer of the same size was cut from the boronized oil pipe of the reference product, and the corrosion resistance of Samples 3 and 4 was tested. Specifically, at 30°C, Samples 3 and 4 were immersed in a NaCl solution with a mass concentration of 10%, and the morphological changes of Samples 3 and 4 were recorded on the first day, the first week, the second week, the third week, and the fourth week, respectively, to obtain Fig.12 as well as Fig.13 .
[0186] pass Fig.12It can be seen that on the first day, there was no change in sample 3 and the NaCl solution. In the first week, the NaCl solution turned light reddish brown. In the second week, the change of sample 3 was not obvious. After weighing, the mass loss of sample 3 at this time was 0.06% compared with that before soaking. In the third week, it was observed that the overall shape of sample 3 was intact. After weighing, the mass loss of sample 3 at this time was 0.10% compared with that before soaking. In the fourth week, it was observed that the color of the NaCl solution deepened, but the shape of sample 3 was still intact.
[0187] pass Fig.13 It can be seen that on the first day, there was no change in sample 4 and the NaCl solution. In the first week, the NaCl solution turned reddish brown. In the second week, oxidative corrosion occurred in sample 4. After weighing, the mass loss of sample 4 at this time was 0.13% compared with that before immersion. In the third week, it was observed that the edge of sample 4 was slightly damaged. After weighing, the mass loss of sample 4 at this time was 0.20% compared with that before immersion. In the fourth week, the color of the NaCl solution was observed to deepen, but the body shape of sample 4 was still intact.
[0188] 3. Nitric acid corrosion resistance:
[0189] A sample with a boronized layer was cut from the boronized oil pipe prepared in Example 2, and recorded as Sample 5. Similarly, a sample 6 with a boronized layer of the same size was cut from the boronized oil pipe of the reference product, and the corrosion resistance of Samples 5 and 6 was tested. Specifically, at 30°C, Samples 5 and 6 were immersed in a HNO3 solution with a mass concentration of 25%, and the morphological changes of Samples 5 and 6 were recorded on the first day, the first week, the second week, and the third week, respectively, to obtain Fig.14 as well as Fig.15 .
[0190] pass Fig.14 It can be seen that on the first day, the edge of sample 5 turned black and a small amount of bubbles appeared in the solution. In the first week, the bubbles in the solution increased and the solution turned dark brown as a whole. In the second week, sample 5 was corroded more severely. After weighing, the mass loss of sample 5 at this time was 28.84% compared with that before immersion. In the third week, it was observed that the carburized layer of sample 5 had completely fallen off and shattered. After weighing, the mass loss of sample 5 at this time was 89.74% compared with that before immersion.
[0191] pass Fig.15It can be seen that on the first day, sample 6 turned black and a large number of bubbles appeared in the solution. In the first week, a large number of bubbles appeared in the solution, the solution turned dark brown as a whole, and the bottom of sample 6 swelled. In the second week, sample 6 was severely corroded. After weighing, the mass loss of sample 6 at this time was 51.91% compared with that before immersion. In the third week, it was observed that the carburized layer of sample 6 had completely fallen off and shattered. After weighing, the mass loss of sample 6 at this time was 94.80% compared with that before immersion.
[0192] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A composite boronizing agent, characterized in that: Including boriding agent and graphite; Wherein, in terms of mass percentage, graphite accounts for 10-14% of the mass of the boronizing agent; the boronizing agent includes the following raw materials in mass percentage: boron supply agent: 10-15%, catalyst: 12-20%, activator: 8-10%, dispersant: 4-6%, filler: 50-55%, flow aid: 8-12%; the dispersant is triethanolamine borate; the boron supply agent is boric anhydride or boron carbide; The catalyst comprises potassium fluoroborate, sodium fluoride and potassium fluoride, wherein potassium fluoroborate accounts for 5-10% of the total mass of the boronizing agent, sodium fluoride accounts for 5-6% of the total mass of the boronizing agent, and potassium fluoride accounts for 2-4% of the total mass of the boronizing agent; The activator includes silicon dioxide and activated carbon, wherein silicon dioxide accounts for 5-7% of the total mass of the boronizing agent, and activated carbon accounts for 2-4% of the total mass of the boronizing agent; the filler includes aluminum oxide and / or silicon carbide.
2. The composite boronizing agent according to claim 1, characterized in that: The particle size of graphite mixed with the boronizing agent is 30-50 mesh; The flow aid includes charcoal powder and graphite powder, wherein the charcoal powder accounts for 3-5% of the total mass of the boronizing agent, and the graphite powder accounts for 4-8% of the total mass of the boronizing agent; the particle size of the graphite powder is 140-160 meshes.
3. A solid boronizing method for oil pipe using the composite boronizing agent according to any one of claims 1 to 2, characterized in that: The steps include: S1: Clean the inner surface of the oil pipe; S2: mixing the boriding agent with graphite to obtain a composite boriding agent, and then filling the composite boriding agent into the oil pipe so that the composite boriding agent contacts the inner surface of the oil pipe; S3: sealing the oil pipe filled with composite boronizing agent; S4: The sealed oil pipe is subjected to a heating boronizing treatment, and after cooling, an oil pipe having a boronized layer on the inner surface is obtained.
4. The solid boronizing method for oil pipe according to claim 3, characterized in that: In step S3, the outer surface of the oil pipe is wrapped with a deoxidizer and metal ceramic balls in sequence, and then the metal ceramic balls are sealed with quartz sand powder.
5. The solid boronizing method for oil pipe according to claim 3, characterized in that: The thickness of the metal ceramic ball layer is 100-150 mm, the particle size of the metal ceramic ball is 1-2 mm, the particle size of the quartz sand powder is 300-350 meshes, and after the quartz sand powder is sealed, the thickness of the quartz sand powder layer is 60-100 mm.
6. The solid boronizing method for oil pipe according to claim 3, characterized in that: In step S4, the heating boriding treatment includes: heating the sealed oil pipe to 660-700°C, keeping it warm for 10-20 minutes, then heating it to 760-800°C, keeping it warm for 5-15 minutes, continuing to heat it to 810-840°C, keeping it warm for 15-25 minutes, then heating it to 850-950°C and keeping it warm for 4-6 hours, and finally cooling it to room temperature to complete the heating treatment.
7. The solid boronizing method for oil pipe according to claim 3, characterized in that: The oil pipe is made of ordinary alloy steel or high alloy steel; In the ordinary alloy steel, the total content of alloying elements is ≤5wt%, In the high alloy steel, the total content of alloying elements is >5wt%.
Citation Information
Patent Citations
Method for boronization surface treatment of workpieces
CN104746001A